Evaluation of distribution characteristics and health risk of polycyclic aromatic hydrocarbons in sediments: From the perspective of land–ocean coordination - Cheng, Jiayi; Wang, Xiaomeng; Zheng, Binghui; Zhang, Xiaoxia; Han, Jianbo (Journal of hydrology (Amsterdam), 2022)
[Display omitted] •A new perspective of land–ocean coordinated analysis was used for PAHs pollution evaluation.•The pollution of PAHs in Liao River and its estuarine posed human around dangerous.•The pollution of PAHs in Liao Estuarine had been deteriorating in recent 20 years.•River and marine PAHs pollution prevention and control management complement each other. Land-ocean coordinated management is an important wisdom for environmental protection and pollution prevention of marine and river systems. Taking Liao River and Estuarine as an example, the pollution characteristics, temporal and spatial distribution and change features of Polycyclic Aromatic Hydrocarbons (PAHs) in sediments in recent 20 years were studied from two different analysis perspectives of land and ocean. The research showed that the pollution of PAHs in the sediments of Liao River and Estuarine was not optimistic. The concentration of Σ16PAHs was 48–28,000 ng/g. The carcinogenic risk to humans shouldn't be ignored, which could cause the loss of life expectancy 0.03–4.2 years. The traceability analysis showed that the use and combustion of fossil fuels were the main sources of PAHs. In addition, the leakage of oil during the intensive transportation of ships in coastal waters might also contribute to PAHs. The concentrations of PAHs had obvious temporal and spatial distribution characteristics. Spatially, estuaries < tributaries < main streams; temporally, wet season < normal season < dry season in Liao River. Whereas, the variation of PAHs in estuarine sediments was slight. In the past 20 years, the concentration of PAHs in Liao River had increased first and then decreased, reaching maximum in 2010; However, the concentration of PAHs seldom decreased in estuarine sediments, in which showed a more serious situation of PAHs pollution control.